A Rare Case of Spontaneous Empyema by Clostridium perfringens - Sijan Basnet; Izza Mir; Elan Mohanty; Rashmi Dhital; Biswaraj Tharu; Dilli Ram Poudel (Case Reports in Infectious Diseases)
Empyema caused by clostridial infections is rare especially in the absence of invasive thoracic procedures. We present the case of an 81-year-old man without a history of preceding trauma who presented with shortness of breath and nonproductive cough and grew Clostridium perfringens only in the pleural cavity. He was predisposed to the infection due to his swallowing dysfunction. He was treated with penicillin and chest tube placement for drainage and subsequently improved.